February 6, 2023 Mw 7.7 Pazarcık earthquake: characteristic features of the surface rupture along the Çakmak Fault (Adıyaman-Gölbaşı-Akçabel) - Akgün, Elif; Softa, Mustafa (Gumushane University, 2025)
This study examines in detail the surface rupture observed between the Gölbaşı district of Adıyaman province and Akçabel town, which resulted from the February 6, 2023, Kahramanmaraş/Pazarcık (Mw: 7.7) earthquake along the East Anatolian Fault System. The deformation along the surface rupture, identified through 1:25,000 scale mapping and field studies, was measured in terms of left-lateral displacement and vertical slip values. These measurements were interpreted in conjunction with a stress state analysis based on instrumental earthquake data. The studies conducted on the surface rupture revealed the following findings: (i) the surface rupture, mapped over approximately 15 km between the Gölbaşı district of Adıyaman province and Akçabel town, aligns with the Çakmak fault defined in this study; (ii) the largest left-lateral displacement and vertical slip values observed along the surface rupture were 425 cm and 102 cm, respectively, near Çakmak town; and (iii) stress analysis indicated that the fault underwent deformation due to the influence of a WNW-ENE extensional force and NNE-SSW compression, consistent with a transtensional tectonic regime. © 2025, Gumushane University. All rights reserved.
6 Şubat 2023 Mw 7.7 Pazarcık depremi: Çakmak Fayı (Adıyaman-Gölbaşı-Akçabel) boyunca yüzey kırığının karakteristik özellikleri
Keywords: East Anatolian Fault System; Pazarcık earthquake; Surface rupture; Çakmak fault